Considerações taxonômicas sobre os Banchinae e revisão das espécies brasileiras de Glyptini (Hymenoptera: Ichneumonidae) - Flórez, Andrés Fabián Herrera (2010)
The Banchinae is a cosmopolitan group of Ichneumonidae comprising three tribes: Atrophini, Banchini and Glyptini; it includes about 50 genera and 1500 described species. The Banchinae generally have long, apically notched ovipositor, a propodeum without or with only a few carinae, and frequently, a tergite I with spiracles located around or before the centre, and the anterior part of the submetapleural carina expanded into a broad lobe. This work is a taxonomic revision of the subfamily Banchinae with emphasis in the tribe Glyptini from Brazil. This tribe is characterized by the possession of oblique grooves on tergites II-IV. This study is based on the main entomological collections of South and Southeastern Brazil; in total more than 3.000 specimens of the subfamily have been examined, not including all of genera already registered to Brazil. Material from 17 of the 27 States of Brazil has been reviewed, although most of the specimens (70.3%) were collected in São Paulo State. The subfamily Banchinae has been registered so far in four kind of Brazilian biomes: Atlantic Forest, Brazilian Savanna, Amazonia and agroecosystems, between 2 and 2.039 m of altitude. The study has revealed the presence in Brazil of 17 genera of Banchinae, one of them is a new genus; 18 new species of the tribe Glyptini are described. Illustrated keys are given to enable the identification of the tribes and the genera of the subfamily Banchinae and the species of the tribe Glyptini from Brazil.